2012
DOI: 10.1111/j.1755-3768.2012.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SofZia‐preserved travoprost and benzalkonium chloride‐preserved latanoprost on the ocular surface – a multicentre randomized single‐masked study

Abstract: ABSTRACT.Purpose: To assess the effect of SofZia-preserved travoprost on ocular surface conditions in comparison with benzalkonium chloride (BAK)-preserved latanoprost. Methods: A prospective randomized multicentre single-masked comparative study. Patients with open-angle glaucoma or ocular hypertension who had been treated with BAK-preserved latanoprost 0.005% (Xalatan Ò ) monotherapy for at least 3 months. Patients were enrolled at 23 facilities. Patients were randomly divided into the X-X group, continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 34 publications
(46 reference statements)
3
51
0
Order By: Relevance
“…There have been reports that sofZia Ò -containing travoprost has a superior safety profile for the ocular surface compared with BAK-containing latanoprost. [15][16][17][18] However, the present study showed that BAK-reduced tafluprost caused less corneal injury than travoprost, thereby indicating that the adverse effects of BAK on the cornea can be alleviated by lowering its concentration, while maintaining its effectiveness as a preservative. In the present study, tafluprost showed better corneal safety than travoprost, which could be attributed to their different cytotoxicities against corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 83%
“…There have been reports that sofZia Ò -containing travoprost has a superior safety profile for the ocular surface compared with BAK-containing latanoprost. [15][16][17][18] However, the present study showed that BAK-reduced tafluprost caused less corneal injury than travoprost, thereby indicating that the adverse effects of BAK on the cornea can be alleviated by lowering its concentration, while maintaining its effectiveness as a preservative. In the present study, tafluprost showed better corneal safety than travoprost, which could be attributed to their different cytotoxicities against corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 83%
“…This toxicity may be the reason for increased expressions of MMPs and TIMPs in the epithelium of glaucoma patients. Further, switching antiglaucoma medication to eye drops that contain a different preservative (Aihara et al 2013) or to preservative-free solutions (Mastropasqua et al 2013;Frezzotti et al 2014) might be beneficial for the maintenance of tissue integrity and health in the superficial parts of the eye. Thus, in addition to long-term treatment with multiple different eye drops, the preservative BAK itself may contribute to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported no significant difference of those prostaglandin drops with and without BAK. 16,24,25 A meta-analysis recently reported that latanoprost is associated with a lower incidence of conjunctival hyperemia than bimatoprost and travoprost in the treatment of ocular hypertension and/or glaucoma. 26 The reason for the reduction in hyperemia caused by latanoprost is likely due to the structure of the latanoprost molecule and its pharmacological receptor profile.…”
Section: Discussionmentioning
confidence: 98%
“…Some researchers have reported that travoprost preserved with SofZia is less toxic to the ocular surface than latanoprost preserved with 0.02% BAK. 10,[13][14][15][16] Tafluprost is also a prostaglandin F2a analog containing 0.001% BAK. BAK is not a chemical with a single structure, but rather a mixture of dodecyl, tetradecyl, and hexadecyl dimethylbenzylammonium chloride.…”
Section: Introductionmentioning
confidence: 99%